Transparent, abrasion-insensitive superhydrophobic coatings for real-world applications. Issue 1 (December 2017) - Helmer, Dorothea; Keller, Nico; Kotz, Frederik; Stolz, Friederike; Greiner, Christian; Nargang, Tobias; Sachsenheimer, Kai; Rapp, Bastian
Abstract Superhydrophobic surfaces and surface coatings are of high interest for many applications in everyday life including non-wetting and low-friction coatings as well as functional clothing. Manufacturing of these surfaces is intricate since superhydrophobicity requires structuring of surfaces on a nano- to microscale. This delicate surface structuring makes most superhydrophobic surfaces very sensitive to abrasion and renders them impractical for real-life applications. In this paper we present a transparent fluorinated polymer foam that is synthesized by a simple one-step photoinitiated radical polymerization. We term this material "Fluoropor". It possesses an inherent nano-/microstructure throughout the whole bulk material and is thus insensitive to abrasion as its superhydrophobic properties are not merely due to a thin-layer surface-effect. Due to its foam-like structure with pore sizes below the wavelength of visible light Fluoropor appears optically transparent. We determined contact angles, surface energy, wear resistance and Vickers hardness to highlight Fluoropor's applicability for real-word applications.